Comparative Study of Total Harmonic Distortion in Multilevel Inverters Based WECS - Kandavel, B; Uvaraj, G; Manikandan, M (International Journal of Engineering and Technology, 2018)
This paper presents comparative study of Total Harmonic Distortion (THD) and its individual harmonic contents without grid and with grid for Diode clamped multi level inverter (DCMLI) and Flying capacitor clamped multilevel inverter (FCMLI) based Doubly Fed Induction Generator (DFIG) employing PI and Fuzzy logic controller (FLC). Simple method to control for a variable speed wind energy conversion system with a DFIG is connected to the grid through a diode rectifier and a diode clamped multilevel inverter (DCMLI). The DC-link voltage is controlled through a DC-DC boost converter to keep the DC voltage at constant value. Inverter is controlled by sinusoidal pulse width modulation technique, which supplies power to the grid. The THD and its harmonic content are studied for different wind speeds. DFIG fed flying capacitor multi level inverter (FCMLI) based WECS connected to load as well as grid. FCMLI is controlled through sinusoidal pulse width modulation. Voltage and current harmonics are studied. The results of both multilevel inverters are compared. It shows that the level of harmonic content of two types of multilevel inverters working at different wind speeds indicates that Total Harmonic Distortion (THD) for DCMLI has given best results.Â Â